Pemberian rewad dalam meningkatkan motivasi belajar siswa pada materi penjumlahan dan pengurangan pecahan di kelas v sd negeri lamsayuen aceh besar - Tara Umaina; Mislinawati Mislinawati; Fauzi Fauzi (Elementary Education Research, 2023)
In the learning process There are numerous students in school make noise and do not hear the teacher's explanation. Lack of enthusiasm of students and students are not enthusiastic in participating in learning. This is due to the lack of student learning motivation. Teachers can use a variety of methods to motivate students to work hard, including offering by using rewards. This study desire to determine the process of giving rewards in increasing motivation for learning in the subject of fraction addition and subtraction in class V SD Negeri Lamsayuen Aceh Besar. The type of descriptive qualitative research used  article is the approach. This article's subordinate is a teacher of class V and 6 students of class V. Information collection techniques are carried out by observation and interviews. All collected data is processed by data analysis stages, namely data reduction, data presentation, and drawing conclusions from all data. Using the data from this study it is known that the provision of rewards can increase student motivation. Those who are already motivated become more active in paying attention to the teacher's explanations in learning activities, look more enthusiastic, more enthusiastic, participate actively and ask questions to the teacher. Rewards are given in the form of (1) praise, (2) respect, (3) prizes, (4) tokens of appreciation. The results of giving rewards have been going well.Kata Kunci: Reward, Motivasi Belajar, Penjumlahan dan Pengurangan.